Comparative morphology and molecular systematics of African Podostemaceae-Podostemoideae, with emphasis on Dickaeanthus and Ledermanniella from Cameroon - Moline, P.; Thiv, M.; Ameka, G.K.; Ghogue, J.P.; Pfeifer, E.; Rutishauser, R. (International Journal of Plant Sciences, 2007)
The Podostemaceae (eudicots, Malpighiales) are adapted to rivers that exhibit distinct high-low water seasonality, mainly in the tropics. They attach to submerged rocks with ribbonlike or crustose green roots that cover the substrate like a carpet. Pronounced root dorsiventrality resulted in disklike crusts lacking root caps. African Podostemoideae show a bewildering array of forms not known from other flowering plants, such as (i) foliage leaves having a basis with two sheaths (e.g., Ledermanniella linearifolia), (ii) modular shoot construction with repeated stem cups (Ledermanniella ledermannii), (iii) endogenous origin of flowers along stems (Dicraeanthus africanus), and (iv) epiphyllous flowers (Ledermanniella letouzeyi). Important morphological transformations specific to African podostemoids include a shift from erect to inverted flowers in the spathella and unilocular ovaries arising via septum loss. New matK sequence data and new morphological data for eight African Podostemaceae species of the genera Dicraeanthus, Djinga, and Ledermanniella are combined with previously published sequences representing all major groups to test the placement of the African taxa in the family. All podostemoids studied from continental Africa form a clade that is sister to the Madagascan genera Endocaulos and Thelethylax. The sister of this African-Madagascan lineage is the clade comprising all Asian podostemoids and the American genus Podostemum, whereas all other New World podostemoids and the subfamily Tristichoideae are more basal. © 2007 by The University of Chicago. All rights reserved.
Keywords: African Podostemaceae; Comparative morphology; Dicraeanthus; Djinga; Ledermanniella; Malpighiales; Molecular systematics; Structural diversity; Water plants